7. CLINICAL CASE REPORT: EFFECTIVENESS OF SKIN INJURY CARE IN STEVENS-JOHNSON SYNDROME (Vietnam Journal of Community Medicine, 2024)
Objective: To describe a clinical case of skin injury care and treatment in Stevens-Johnson Syndrome at the Department of Intensive Care and Toxicology, Thu Duc City Hospital.Case Report: The patient is a 47-year-old female admitted with a diagnosis of acute cholecystitis due to gallstones and underwent gallbladder drainage in the General Surgery Department. On the 6th day of hospitalization, the patient developed skin redness, blistering, generalized edema, and fever.Results: The diagnosis was Stevens-Johnson Syndrome, suspected to be caused by the use of Acupan, along with sepsis originating from the biliary tract and acute cholecystitis due to gallstones, which had been drained. The patient was transferred to the Department of Intensive Care and Toxicology. After 12 days of treatment, in addition to medication, mucosal care, continuous pain management, and other systemic supportive therapies, the patient's skin injuries healed well, the skin redness did not progress, mucosal injuries improved, and blood test abnormalities were resolved.Conclusion: The combination of medication, mucosal injury care, continuous pain management, and other systemic supportive treatments showed positive effectiveness in the care of skin injuries in Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TEN).
Keywords: Stevens-Johnson; care effectiveness; skin injury